2020
DOI: 10.9734/jamb/2020/v20i930279
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Polyhydroxyalkanoates from Lactic Acid Bacteria Isolated from Dairy Wastewater, Fermented Cow Milk and ‘Ogi’

Abstract: Aims: This study aimed at screening, producing and characterizing polyhydroxyalkanoates (PHA) from lactic acid bacteria (LAB) isolated from dairy wastewater, fermented cow milk and “ogi”. Place and Duration of Study: Department of Microbiology, Faculty of Science, University of Ibadan, Ibadan between August 2018 and February 2019. Methodology: The initial screening of isolated LAB was carried out by Sudan Black staining method followed by secondary screening on liquid medium. Isolates that tested p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Recently, some probiotics, such as Bacillus subtilis and lactobacillus , have been engineered to produce PHA of high production yield ( Singh et al, 2009 ; Monilola and Makinde, 2020 ). Interestingly, Yan et al showed proven success in colitis treatment by engineering the synthesis pathway of 3HB, the natural unit of PHB, in probiotic Escherichia coli Nissle 1917 ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some probiotics, such as Bacillus subtilis and lactobacillus , have been engineered to produce PHA of high production yield ( Singh et al, 2009 ; Monilola and Makinde, 2020 ). Interestingly, Yan et al showed proven success in colitis treatment by engineering the synthesis pathway of 3HB, the natural unit of PHB, in probiotic Escherichia coli Nissle 1917 ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the nature of the repeating unit, biopolymers can be classified into groups like polysaccharides, glycolipids, lipopolysaccharides, proteins, etc. [ 8 , 13 , 14 , 15 ].…”
Section: Classification Of Biopolymers Produced By Lactic Acid Bacteriamentioning
confidence: 99%
“…Biopolymers can be synthesized by plants, animals, and microorganisms [ 13 , 16 ]. Lactic acid bacteria (LAB) are capable of producing biopolymers with very different chemical structures, grouped into exopolysaccharides (EPSs), polyhydroxyalkanoates (PHAs), and polylactic acid (PLA) [ 8 , 14 , 15 ].…”
Section: Classification Of Biopolymers Produced By Lactic Acid Bacteriamentioning
confidence: 99%
See 2 more Smart Citations